KELAS SEHAT LANSIA DALAM MENGENAL PERMASALAHAN PADA KASUS MUSKULOSKELETAL - Dea Linia Romadhoni; Alinda Nur Ramadhani; Maskun Pudjianto (P3M Universitas Aisyiyah Surakarta, 2021)
The problem of the elderly group in the Posyandu Lansia Aisyiyah Banjarsari Surakarta based on the result of observation and survey is the lack of awareness of the elderly in maintaining health that can lead to geriatric condition, especially musculoskeletal health problems. Based on these problems, the solution offered to the partner group is assisting the elderly by providing health education. Health education program by a healthy elderly class consisting of health education, regular health condition check-up, early detection, intervention of geriatric problems, and recreation functional activities. Sustainable assistance is provided through healthy elderly class. Output that will be produced through this program are booklet and journal. Result of this program is an increase in elderly knowledge about musculoskeletal problems such as Osteoarthritis, Rheumatoid arthritis, Osteoporosis and Low Back Pain. Conclusion of this community service is that the activity that have been carried out get positive and good response by the cadres and elderly. After attending the ederly class activities, the elderly learn about musculoskeletal cases in elderly, prevention and treatment in musculoskeletal disorder.